2017
DOI: 10.1177/0261018317746042
|View full text |Cite
|
Sign up to set email alerts
|

Gender, work and care in policy and practice: Working mothers’ experience of intergenerational exchange of care in South Korea

Abstract: This article aims to uncover working mothers' experiences in relation to intergenerational exchange of care and support in South Korea. It examines the impact of Confucian gender ideology on the operation of intergenerational reciprocity within the Korean family. Increasing numbers of working mothers make intergenerational exchange of care between working mothers and their family members an important issue. Although studies have focused on the importance of the Confucian virtue of filial piety in intergenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Family intergenerational exchanges maintain bidirectional, dynamic, and continuous transmissions [24]. As resources and power flow between generations, current support helps motivate future intergenerational exchanges [18].…”
Section: Social Exchange Theory and Demonstration Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Family intergenerational exchanges maintain bidirectional, dynamic, and continuous transmissions [24]. As resources and power flow between generations, current support helps motivate future intergenerational exchanges [18].…”
Section: Social Exchange Theory and Demonstration Effectmentioning
confidence: 99%
“…In line with previous evidence, our results showed that traditional gender roles are salient [47], especially regarding more age characteristics, family function, and family intimacy. Traditionally, women have played the role of primary family caregivers, especially in Confucian cultures in Eastern countries [18]. Compared to men, women take on more responsibility for household chores and provide more care for grandchildren.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation